Peroxisome proliferator-activated receptor α activation regulates lipid metabolism in the feto-placental unit from diabetic rats - Martinez, Nora Alicia (2008)
Maternal diabetes promotes an overaccumulation of lipids in the feto-placental unit and impairs feto-placental development and growth. Here, we investigated the role played by the nuclear receptor peroxisome proliferator-activated receptor (PPAR)α in lipid metabolism in fetuses and placentas from control and neonatal streptozotocin-induced diabetic rats. Placentas and fetuses were studied on day 13.5 of gestation. The concentrations of PPARα (by Western blot) and its endogenous agonist leukotriene B4 (LTB4) (by enzyme immunoassay) were analysed. Placental explants and fetuses were cultured with LTB4 or clofibrate, and then lipid metabolism analysed (concentrations and synthesis from 14C-acetate of triglycerides, phospholipids, cholesterol and cholesteryl esters; release of glycerol and free fatty acids (FFAs)). We found that maternal diabetes led to increases in placental concentrations of triglycerides and cholesteryl esters, and fetal concentrations of phospholipids. PPARα agonists downregulated fetal and placental lipid concentrations in control and diabetic rats. The synthesis of lipids was reduced in the diabetic placenta but increased in fetuses from diabetic animals. PPARα agonists reduced the synthesis of lipids in control placenta and in the fetuses from control and diabetic rats. Glycerol and FFA release was enhanced in the diabetic placenta and in control placenta cultured with PPARα agonists. Maternal diabetes led to reductions in fetal and placental LTB4 concentrations and to increases in placental PPARα concentrations. Overall, these data support a novel role of PPARα as a regulator of lipid metabolism in the feto-placental unit, relevant in maternal diabetes where fetal and placental PPARα, LTB4 and lipid concentrations are altered.